Extremely Preterm Infants and Neurologic Disability - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2000)
Of 308 surviving children, born at 25 or fewer weeks of gestation in the United Kingdom and Ireland, 283 (92%) were examined at a median age of 30 months, and results reported from the School of Human Development, University of Nottingham, UK.